TINJAUAN KARDIOMIOPATI DILATASI (DCM) TERHADAP KUALITAS HIDUP ANJING RAS BESAR - Sayyidah Auliyaur Rohmah; F Mela Eka Nuri CAHYANI; Ira Zakia SALSABILA (RADINKA JAYA UTAMA PUBLISHER, 2024)
Dilated cardiomyopathy (DCM) is a condition in which the heart enlarges and cannot pump blood efficiently, characterized by dilation of the ventricles, especially the left ventricle. Dilated cardiomyopathy is most common in dogs, both large and small breeds. The purpose of this review is to determine the quality of life of dogs with dilated cardiomyopathy, what causes it, how to treat it properly and optimally, and efforts to prevent dilated cardiomyopathy. This study uses a bibliographic method. Extensive research for studies published before 2024 was conducted using two databases: PubMed and Google Scholar. Dilated cardiomyopathy can occur due to several causes such as genetic or hereditary factors, hypertension, injury, metabolic defects, infection, myocardial ischemia, and toxicity. These factors also affect the survival of dogs with DCM. Thus, preventive efforts to overcome DCM must be carried out. Such as maintaining nutrition, exercising regularly, maintaining body weight, and vaccination.